Quebec Community Groups Network Welcomes Government of Canada's Investment in Quebec's English-speaking Communities - Quebec Community Groups Network (QCGN) (2005)

The Twenty-Fourth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2005)

Training and Human Resources Development Project : Measure 1 : Language training program - Dialogue McGill (2005)
The language training program presented is part of the Training and Human Resources Development Project that McGill University is to implement. This project is designed to ensure that English-speaking Quebecers obtain equitable access, in their language, to the range of health and social services offered to the entire population. The project has been elaborated against a backdrop of sociodemographic changes affecting Québec’s English-speaking communities, the adoption of new legislation modifying the organization of work, and the modernization of the health and social services system. It will be geared to clinical projects now being prepared pertaining to the organization of services. The project is an additional means of reviewing and implementing regional programs of access to health and social services in the English language, as stipulated by the Act respecting health services and social services.

Cultural Brief Presented to the City of Montreal February 11, 2005 as Part of the Development Process for the New Culture Policy - English Language Arts Network (ELAN) (2005)
Montreal is one of the world's major French-speaking cities. It is also home to a large and active population of English-speaking artists that is stimulated by the city's dynamic cultural environment. The vast majority of English-speaking artists live in and around the Metropolis. Therefore they have a vested interest in actively participating in Montreal's development.

Community NetLink - Community Health and Social Services Network (CHSSN) (2005)

Community NetLink - Community Health and Social Services Network (CHSSN) (2005)

Listening to Our Young People : The VEQ Youth Report 2005 - Pitre, Edgard; Tomlinson, Patrick; Twardawa, Christopher (Voice of English-speaking Quebec (VEQ), 2005)
The following represents the findings of a youth study conducted by the Voice of English-speaking Québec (VEQ) in 2004 - Listening to Our Young People. The purpose of the study was to collect and correlate survey responses completed by Secondary IV and V, adult learning centre, and CEGEP 1, 2 and 3 Anglophones in the Greater Quebec City and Chaudières-Appalaches regions. The survey questions varied in scope but the general focus was concerned with the various aspects of daily life in and around Quebec City. By analyzing survey responses, VEQ hoped to arrive at a better understanding of the perceptions, positive and otherwise, young Anglophones have regarding their community.

Strategic Plan : 2005-2006 to 2008-2009 - The English Speaking Catholic Council (ESCC) (2005)